Solving cell infiltration limitations of electrospun nanofiber meshes for tissue engineering applications - Guimarães, Ana Cristina Silva Esperança (2010)
AIM: Utilize the dual composition strategy to increase the pore size and solve the low cell infiltration capacity on random nanofiber meshes, an intrinsic limitation of electrospun scaffolds for tissue engineering applications. MATERIALS & METHODS: Polycaprolactone and poly(ethylene oxide) solutions were electrospun simultaneously to obtain a dual composition nanofiber mesh. Selective dissolution of the poly(ethylene oxide) nanofiber fraction was performed. The biologic performance of these enhanced pore size nanofibrous structures was assessed with human osteoblastic cells. RESULTS: The electrospun nanofiber meshes, after the poly(ethylene oxide) dissolution, showed statistically significant larger pore sizes when compared with polycaprolactone nanofiber meshes with a similar polycaprolactone volume fraction. This was also confirmed by interferometric optical profilometry. Using scanning electron microscopy and laser scanning confocal microscopy, it was observed that osteoblastic cells could penetrate into the nanofibrous structure and migrate into the opposite and unseeded side of the mesh. CONCLUSION: An electrospun mesh was created with sufficient pore size to allow cell infiltration into its structure, thus resulting in a fully populated construct appropriate for 3D tissue engineering applications.